2022
DOI: 10.3390/ijerph19159091
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Complex Multimorbidity in India: Findings from the 2017–2018 Longitudinal Ageing Study in India (LASI)

Abstract: Complex multimorbidity refers to the co-occurrence of three or more chronic illnesses across >2 body systems, which may identify persons in need of additional medical support and treatment. There is a scarcity of evidence on the differences in patient outcomes between non-complex (≥2 conditions) and complex multimorbidity groups. We evaluated the prevalence and patient outcomes of complex multimorbidity and compared them to non-complex multimorbidity. We included 30,489 multimorbid individuals aged ≥45 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Previous studies indicated that the prevalence of multimorbidity was higher among rural older adults [ 20 , 34 ]. A study conducted in India found that participants residing in urban areas were more likely to report complex multimorbidity [ 35 ]. These inconsistencies may be partly due to the differences in sampling size and chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the prevalence of multimorbidity was higher among rural older adults [ 20 , 34 ]. A study conducted in India found that participants residing in urban areas were more likely to report complex multimorbidity [ 35 ]. These inconsistencies may be partly due to the differences in sampling size and chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the governance scheme for the health poverty vulnerability of rural elderly families should focus on improving the family coping ability. Primary care facilities should be strengthened to increase availability and accessibility while making the facilities affordable ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, “race/ethnicity”, a social construct that is relevant in the U.S., does not have a direct equivalent in India. Therefore, in place of race/ethnicity, we utilized “caste”, a group based on social class hierarchy in India, and “religion”, with sub-categories of Hindu, Muslim, Christian, and others, the latter three being minority religions in a secular India [ 9 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have reported the multimorbidity in India to be as much as 50% or higher among older adults ≥45 years [ 3 , 4 , 5 ]. Previous studies focused on aging in India have reported that the prevalence of multimorbidity- to increases with age and socioeconomic status (SES) [ 3 , 9 , 10 ]. For example, the prevalence of multimorbidity as reported in the urban poor sub-population who were ≥75 years old was higher than in the 60–74 age group or the 45–59 age group in India (64.14 vs. 53.41 vs. 33.83) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%